A NOVEL PROTOTYPING APPROACH TO BROADBAND MICROSTRIP 90 DEGREES PHASE SHIFTERS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This work presents o series of computer modeling experiments conducted with the goal of streamlining the synthesis of a family of broadband microwave 90 degrees phase shifters. While most broadband microwave phase shifters based on segments of coupled transmission lines were initially designed with symmetric transmission lines, current approaches require to adapt such designs to microstrip lines. The proposed approach includes the development of simple mathematical models for three representative 90 degrees phase shifters and the employment of available MATLAB genetic optimization algorithms for synthesizing the microstrip lines included in the phase shifters. The results are validated by implementing the synthesized circuit in Ansys CIRCUIT and further improved by developing and optimizing more detailed models in Ansys HFSS.
Keywords: Déphaseurs micro-ondes; Prototypage; Section C; Lignes couplées microruban; Matrice d'impédance; Algorithme génétique; Déphaseur de Schiffman